Clinical, Immunological, and Molecular Profile of Chronic Granulomatous Disease: A Multi-Centric Study of 236 Patients From India - Rawat, Amit; Vignesh, Pandiarajan; Sudhakar, Murugan; Sharma, Madhubala; Suri, Deepti; Jindal, Ankur; Gupta, Anju; Shandilya, Jitendra Kumar; Loganathan, Sathish Kumar; Kaur, Gurjit; Chawla, Sanchi; Patra, Pratap Kumar; et al. (Frontiers in Immunology, 2021)
Background: Chronic Granulomatous Disease (CGD) is an inherited defect in phagocytic respiratory burst that results in severe and life-threatening infections in affected children. Single centre studies from India have shown that proportion of autosomal recessive (AR) CGD is more than that reported from the West. Further, affected patients have high mortality rates due to late referrals and difficulties in accessing appropriate treatment. However, there is lack of multicentric collaborative data on CGD from India. Objective: To describe infection patterns, immunological, and molecular features of CGD from multiple centres in India. Methods: A detailed proforma that included clinical and laboratory details was prepared and sent to multiple centres in India that are involved in the care and management of patients with inborn errors of immunity. Twelve centres provided data which were collated and analysed. Results: Of the 236 patients in the study, X-linked and AR-CGD was seen in 77 and 97, respectively. Male female ratio was 172:64. Median age at onset of symptoms and diagnosis was 8 and 24 months, respectively. Common infections documented include pneumonia (71.6%), lymphadenitis (31.6%), skin and subcutaneous abscess (23.7%), blood-stream infection (13.6%), osteomyelitis (8.6%), liver abscess (7.2%), lung abscess (2.9%), meningoencephalitis (2.5%), splenic abscess (1.7%), and brain abscess (0.9%). Forty-four patients (18.6%) had evidence of mycobacterial infection. Results of molecular analysis were available for 141 patients (59.7%) – CYBB (44.7%) gene defect was most common, followed by NCF1 (31.9%), NCF2 (14.9%) and CYBA (8.5%). While CYBA variants were documented only in Southern and Western parts of India, a common dinucleotide deletion in NCF2 (c.835_836delAC) was noted only in North Indian population. Of the 174 patients with outcome data, 67 (38.5%) had expired. Hematopoietic stem cell transplantation was carried out in 23 patients and 12 were doing well on follow-up. Conclusions: In India, AR-CGD is more common compared to Western cohorts, though regional differences in types of AR-CGD exist. Clinical profile and mortality rates are similar in both X-linked and AR-CGD. However, this may be a reflection of the fact that milder forms of AR-CGD are probably missed. Keywords: Chronic Granulomatous Disease; India; Mycobacterium tuberculosis; BCG; Survival